The Effect Of Price Perception And Product Completeness On The Decision To Purchase Heavy Equipment Spare Parts At CV. Chatra Power Part In Pekanbaru - Octavia, Putri; Mulyana, Sri; Susanti, Desi (International Journal of Social Sciences, 2025)
This study aims to determine the Influence of Price Perception and Product Completeness on Purchase Decisions for Heavy Equipment Spare Parts at CV Chatra Power in Pekanbaru. This study is a quantitative study with variables of price perception and product completeness on purchasing decisions. This study uses a data collection technique by distributing questionnaires. The number of samples in this study was 55 respondents taken using the slovin technique. The data analysis technique used is descriptive statistical analysis and inferential statistical techniques using the validity test formula, reliability, classical assumption test, multiple linear regression, t-test, F-test, and coefficient of determination. The results of the study indicate that price perception has a significant effect on purchasing decisions and product completeness has a significant effect on purchasing decisions. While price perception and product completeness have a significant effect on purchasing decisions. Then it is also known that the contribution of the presentation of the influence given by price perception and product completeness is 54.8% and the remaining 45.2% comes from other variables not included in this study. And it can be concluded that price perception and product completeness have an effect on purchasing decisions for heavy equipment spare parts at CV Chatra Power Part in Pekanbaru